Jim T. Reed. Genesis: The Making of Literary Works from Homer to Christa Wolf. Camden House, 2020. - Chiedozie M Uhuegbu (Studies in 20th & 21st Century Literature, 2022)
Review of Jim T. Reed. Genesis: The Making of Literary Works from Homer to Christa Wolf. Camden House, 2020. 301 pp.
Keywords: Genesis; Jim Reeds; Literary works; authorship